Nationalization (expropriation) of foreign investors’ property: relevant issues - A. E. Evstratov; I. Yu. Guchenkov (Правоприменение)
The subject. Foreign investments in the economy of states play an important role. As a consequence, priority should be given to the protection of foreign investments and the creation of favorable and stable conditions for the investors activities. This is especially important in cases of an unfavorable political environment, various internal and external conflicts. Crossborder investment activity is risky, and one of the possible risks is the nationalization (expropriation) of the property of foreign investors by the state-recipient of investments. This method of seizing private property is regulated by the state both at the international legal level and at the national level. The institution of (nationalization) expropriation of the property of foreign investors has its own specifics in Russian legislation in terms of terminological features and legal regulation with certain problematic aspects inherent in it.The purpose of the article is to determine the content and correlation of the concepts of "nationalization" and "expropriation" in Russian law; to describe the main international approaches to regulation of these issues as well as Russian model. The authors try to describe the existing problems inherent in this institution in private international law in general and in Russian legislation in particular and suggest possible ways to solve them.The methodology. The research was carried out using formal-logical, systemic, comparative, formal-legal methods, analysis and synthesis.The main results, scope of application. The content and correlation of the concepts "nationalization" and "expropriation" in Russian law is determined, it is proposed to consider them synonymous. International approaches to regulating the nationalization (expropriation) of the property of foreign investor are examined. The regulation of this institution in Russia is considered; certain problems inherent in nationalization (expropriation) are investigated, possible ways to solve them are suggested.Conclusions. It is now necessary not only to create conditions for attracting foreign investments, but also to ensure their safety in view of the development of cross-border investment activities. In particular, this can be achieved by establishing a detailed regulated procedure for the nationalization (expropriation) of the property of foreign investors, providing guarantees of compensation and legality in such seizure of their property. The institution of nationalization (expropriation) of property in private international law should be considered as one of the possible risks in the implementation of investment activities, which means that states should take measures to minimize risks in order to increase investment attractiveness. It can be achieved through detailed legislative regulation at the national level and a conclusion of international treaties (the “force of law” should be upheld, not the “law of force”).